3x-5(5x-9)=

Simple and best practice solution for 3x-5(5x-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5(5x-9)= equation:


Simplifying
3x + -5(5x + -9) = 0

Reorder the terms:
3x + -5(-9 + 5x) = 0
3x + (-9 * -5 + 5x * -5) = 0
3x + (45 + -25x) = 0

Reorder the terms:
45 + 3x + -25x = 0

Combine like terms: 3x + -25x = -22x
45 + -22x = 0

Solving
45 + -22x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-45' to each side of the equation.
45 + -45 + -22x = 0 + -45

Combine like terms: 45 + -45 = 0
0 + -22x = 0 + -45
-22x = 0 + -45

Combine like terms: 0 + -45 = -45
-22x = -45

Divide each side by '-22'.
x = 2.045454545

Simplifying
x = 2.045454545

See similar equations:

| 8nk-7mn=11m | | 4(x-2)+5(x+4)=-7 | | 7(x+1)=8x-7 | | 4(5r-7)+9(r+2)= | | 9a-12-11a+9= | | 9p-11-18p+7= | | 6y+(-8y)= | | 5(4-2x)=2(x-2) | | 15a-6a+9a+b= | | 12x^3-4x^2+2x+8=0 | | 5+y=70 | | 4x+5=3x+2 | | 4x-6=2(2x+3) | | x^4+2x^3-19x^2-8x+60=0 | | 60/60=60(5280)/60 | | x^3-2x^2-4x+12=0 | | 5z-(7x+7)=9 | | 3N+2b=c | | 4x+(-4)=-6 | | 11-8x=51-36x | | -144-7x=10x+22 | | 5x^3+2x^2+8x-10=0 | | 4v-5v=-4 | | 9a-4=41 | | 9a-4=4 | | 5x+1x=-3 | | 4(3x+2)-4= | | x^3-3x^2-7x+a=0 | | 3x=25-y | | 5=4x-9+x-3x | | X-4=0.5X | | 100=2x-x+4x |

Equations solver categories